Doctor’s Attitudes towards Suicide Attempters: A Comparative Study of Physicians, Surgeons and Psychiatrists - Syeda Ayat-e-Zainab Ali; Tamkeen Saleem (International Journal of Business and Economic Affairs, 2024)
Attitudes towards individuals who attempt suicide are crucial in determining whether patients seek help and receive appropriate care. With an increasing number of patients with suicidal behavior being treated by doctors in general hospitals, this study aimed to compare the attitudes of physicians, surgeons, and psychiatrists towards these patients. Additionally, the study examined differences in attitude towards attempters across doctor’s working more or equal to ten hours’ a day. A cross-sectional comparative study was conducted with a sample of 150 doctors (50 from each specialty) from Benazir Bhutto Hospital, Pakistan Institute of Medical Sciences, Fauji Foundation Hospital, CMH, Watim Medical Hospital, CDA Hospital, Pakistan Ordinance Factories Hospital, and Shifa International Hospital. Data were collected using a demographic sheet and the Understanding Suicidal Patients Scale to measure attitudes towards those who attempt suicide. Analysis was performed using SPSS (Version 25). Participants were aged 25-35 (56.6%), 36-45 (39.3%), and 46-55 (4.1%). The sample included a slightly higher proportion of females (50.7%) than males (49.3%), with 92.6% identifying as Muslim and 7.4% as Christian. A majority (60.7%) belonged to the middle socio-economic status, 44.8% were married, and 62.0% lived in nuclear families. Additionally, 57.4% of participants worked more than 10 hours per day. The results indicated that psychiatrists exhibited a significantly more positive attitude towards suicide attempters compared to physicians and surgeons (p<.001). Furthermore, doctor’s working more than 10 hours a day demonstrated more negative attitudes towards these patients than those who worked 10 hours (p<.03). These findings suggest that to provide better treatment to patients in need, suicide prevention programs must be combined with medical training and support.